Peran Kelompok Sadhar Wisata Dalam Pengembangan Wisata Air Di Desa Jogotirto, Berbah, Sleman, Daerah Istimewa Yogyakarta - Wisnu Hadi (Media Wisata, 2017)
Yogyakarta Special Region which has interesting places of interest and become a good potential to grow DIY citizen reconstruction. Tourism development efforts in each tourist attraction has been done to become an attractive destination for people who want to visit and recreation. One of them is the potential of the famous Water Tour is the water tour Lava Bantal and Embung Tegal Tirto existing Jogotirto Village, Berbah, Sleman, Daerah Istimewa Yogyakarta. The Role of Awareness Group of Tourists in Water Tourism Development That is Lava Bantal and Embung Tegal Tirto In Jogotirto Village, Berbah, Sleman, Special Region of Yogyakarta which has been developing water tourism object to become a destination place in Yogyakarta. Qualitative descriptive research with data retrieval through interview techniques to the actors of tourism that is the group of tourism awareness that developed the water tourism Embung Tegal Tirto and Lava Bantal and the spread of questionnaires to tourists who come to the water tour to know the responses of tourists to the Role of Group Conscious Tourism In Water Tourism Development In Jogotirto Village, Berbah, Sleman, Daerah Istimewa Yogyakarta. From the results of the questionnaire that 51.6% of tourist wisatwan asses s infrastructure facilities in tourism is good enough. Lava Bantal as a water tour is considered clean enough where as many as 60% of tourists in addition to the Lava Bantal business to create a sense of security is running well, where visitors always diterjaminnya vehicle while parked and quiet while enjoying the scenery in the object this is said to visitors as much 50%. Devices and citizens have kept objects well.